Kebijakan Anti Dumping dan Trade Deflection: Studi Kasus Synthetic Staple Fibre Polyester (PSF) - Rukmini, Wara Agustina; Irawan, Ferry (UI Scholars Hub, 2009)
This research empirically examines whether a country's anti dumping policy can distort export of another country to third markets. This research tries to explore about trade deflection of Indonesia's export on Synthetic Staple Fibre Polyester (PSF) HS 550320 to non-European Union as the result of European Union's (EU) anti dumping policy on Indonesia. This research uses panel data model (fixed effects) and 20 countries (non-European Union) of Indonesia's PSF export during ten years (1996-2005). We find evidence that trade deflection for Indonesia's export on Synthetic Staple Fibre Polyester (PSF) HS 550320 occurred. Because of European Union had imposed anti dumping duty on Indonesia, Indonesia's export to non European Union had increased ranged from 25 percent to 44 percent. This result shows that anti dumping duty from European Union does not fully carry out negative effect for Indonesia, furthermore this phenomena can be used as